Slavery, philosophy, and American literature, 1830-1860 - Lee, Maurice S (Cambridge University, 2013)
Maurice S. Lee demonstrates for the first time how the slavery crisis became a crisis of philosophy that exposed the breakdown of national consensus and the limits of rational authority. Poe, Stowe, Douglass, Melville, and Emerson were among the antebellum authors who tried - and failed - to find rational solutions to the slavery conflict. Drawing on antebellum moral philosophy, political theory, and metaphysics, Lee brings a fresh perspective to the literature of slavery to argue that romantic, sentimental, and black Atlantic writers all struggled with modernity when facing the slavery crisis.